Diatom motility and nuclear alterations are affected by sediment elutriates of agricultural streams - Nicolosi Gelis, María Mercedes (2020)
Diatoms respond to toxicants in lotic systems, and they are commonly considered to be sensitive indicators in environmental safety assessment. In addition to the structural characteristics of the algal populations, recent studies have shown that endpoints such as nuclear anomalies or diatom motility measures can be affected quickly by environmental changes. We sought to determine if cell density, cell size, nuclear anomalies and motility of the diatom Nitzschia palea were useful indicators of sediment quality from agricultural streams. For this purpose, we exposed cultures of the diatom to elutriates from sediments of a stream that flows through an intensive agricultural area, and measured the responses of the populations for 7 days in laboratory tests. The bioassays showed that motility measures in Nitzschia palea and the condition of their nuclear membranes rapidly reflected the effects of sediment quality after only 48 h of exposure; mean cell density and length were affected by day 7. The sediment elutriates affected cell movements by shortening the total path length and decreasing cell velocity; they also increased the number of cells with nuclear membrane breakage. Our results from these bioassays show that diatom motility measurements and the condition of the nuclei might be indicators that respond faster to impacts than the traditional structural parameters, such as cell density, specific composition of the assemblage or diversity metrics of the algal communities more often used in biomonitoring.